AGROPRENEURSHIP SEBAGAI SARANA PEMBELAJARAN AL-ISLAM DAN KEMUHAMMADIYAHAN: STUDI KEGIATAN PENANAMAN SAWI DAN UBI - Aisyah Mega; Bryan Khalil; Siti Najwa; Bhunga Shazkia; Anny Hanifah; Anisa Humaira; Aisril Eka; Camelia Camelia; Aulia Zahra; Aulia Fathannisa; Aulia Nur Farida (Jurnal Padamu Negeri, 2026)
Agropreneurship is an approach that integrates agricultural activities with entrepreneurial principles to enhance value added, economic independence, and food security. In the educational context, agropreneurship has the potential to serve as a contextual learning medium that not only develops entrepreneurial skills but also instills character and Islamic values. This study aims to examine the role of agropreneurship as a learning approach for Al-Islam and Kemuhammadiyahan through mustard greens and sweet potato cultivation activities. The research employed an observational method with a qualitative approach, conducted through direct observation of students’ processes, participation, and behavior during the planting activities. The results indicate that agropreneurship activities improve students’ understanding of agricultural entrepreneurship practices, foster independence, hard work, and responsibility, and internalize Al-Islam and Kemuhammadiyahan values such as trustworthiness (amanah), Islamic brotherhood (ukhuwah), and ecological awareness. Therefore, agropreneurship can be applied as a holistic and practical learning approach in Al-Islam and Kemuhammadiyahan education to develop students who are faithful, knowledgeable, and entrepreneurial-minded.